Model of Mathematical Creative Thinking Ability Based on Character Education for Elementary School Students Jakarta - Manurung, Alberth Supriyanto; Halim, Abdul; Nur, Syurya Muhammad (Asatiza: Jurnal Pendidikan, 2024)
The ability to think creatively mathematically is the basis for students solving mathematical problems. Based on initial observations made on students at SDN Duri Kepa 05 Pagi Jakarta, it was revealed that working on mathematics problems was a problem, therefore a creative learning model was needed to train students' creative thinking abilities. Thus, the ability to think creatively mathematically can be used as an alternative solution to educational problems. This research aims to analyze the mathematical creative thinking abilities of fifth grade students through character education for students in elementary schools. The type of research used is comparative causal research, also called ex-post facto research with a quantitative approach. The respondents in this study were 32 class V students. Data analysis in this research uses descriptive and inferential statistics in the form of simple linear regression analysis. Based on the research results, it shows that student character education can significantly improve their mathematical creative thinking abilities. Students' mathematical creative thinking abilities are influenced by students' character education by 68.7%. Meanwhile, 31.3% was influenced by other factors outside of students' character education.